Edukasi Tantangan Transformasi Digital di Dunia Bisnis pada Masyarakat Dapil Sumatera Selatan 2 - Sejahtera Surbakti, Feliks Prasepta (LPPM Universitas Bina Sarana Informatika, 2024)
Digital transformation has become an essential aspect of economic development and modern society, especially in Indonesia, which is currently a leading player in the ASEAN digital economy. A 2022 study by Google Temasek Bain & Company showed that Indonesia contributes around 40% of the total value of digital economy transactions in ASEAN. One of the challenges of digital transformation in Indonesia lies in the use of information and communication technology in business processes and community activities. This community service project aims to analyze the main challenges in digital transformation in Indonesia's business sector, particularly in utilizing information and communication technology to improve business efficiency. The method used is a national webinar-based community service involving legislators, academics, and practitioners, with an awareness-raising approach through presentations and interactive discussions. The results of this activity show that public awareness of the challenges of digital transformation increased by 70%, with participants gaining a better understanding of the importance of strategies in utilizing digital technologies, such as social media, data analytics, and artificial intelligence (AI). In conclusion, digital transformation is an urgent necessity to enhance business competitiveness in the digital economy era, with the involvement of diverse stakeholders being key to addressing these challenges.